Bacterial endophytome sources, profile and dynamics—a conceptual framework - Lengrand, Salomé; Pesenti, Lena; Bragard, Claude; Legrève, Anne (Frontiers in Sustainable Food Systems, 2024)
Currently, it seems inconceivable to dispute the major role of microorganisms in human health or insects with endosymbionts. Although microbial endophytes were discovered long ago, little is known about the roles of plant-associated microorganisms. Some endophytes are horizontally transmitted, whereas others are seed-borne; together, they influence plant health. Beneficial endophytes can promote plant growth and yield by increasing plant resistance to biotic and abiotic stresses. Recently, the tools available to study the phytobiome have much improved, opening doors for a better understanding of the fascinating interactions taking place at the plant level. This review redefines the conceptual framework for “endophyte” and “endophytome,” focusing on the intricate dynamics of bacterial endophytomes. Systematically examining the formation pathways and profiling endophytes allows for a comprehensive exploration of the intricate dynamics governing plant-microbe interactions. Additionally, the assessment of how endophytomes are influenced by both biotic and abiotic factors provides essential insights into the adaptability and resilience of plant-associated microorganisms. Our comprehensive analysis integrates genomic insights with environmental considerations, offering a nuanced perspective on the functional roles of bacterial endophytomes. Therefore, a new, inclusive definition is essential to accurately represent the complexity of interactions within the plant microbiome as well as having the whole picture of associated concepts.